2018
DOI: 10.3389/fpls.2018.00714
|View full text |Cite
|
Sign up to set email alerts
|

The Response of Photosynthetic Functions of F1 Cutting Seedlings From Physocarpus amurensis Maxim (♀) × Physocarpus opulifolius “Diabolo” (♂) and the Parental Seedlings to Salt Stress

Abstract: This paper selected clonal cutting seedlings from the F1 hybrid varieties of Physocarpus amurensis Maxim (♀) × P. opulifolius “Diabolo” (♂) as research material to study the response of the photosynthetic gas exchange parameters and chlorophyll fluorescence parameters of P. amurensis hybrids and their parental leaves to NaCl stress (with concentrations of 0, 50, 100, and 200 mmol⋅L-1). The results showed that under salt stress, the stomatal conductance (Gs), transpiration rate (Tr), and net photosynthetic rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…In this study, we found that the hybrid of B. napus resulted in the promotion of seed germination and seedling growth under salt stress (Figures 1A-D), which were confirmed by the alleviation of reduction in plant height (Figure 1E), chlorophyll (Figure 1F), relative water content (Figure 1G), and biomass (Figure 1H). These results in B. napus were consistent with previous studies (Akram et al, 2010;Fujimoto et al, 2012;Bagum et al, 2017;Xu et al, 2018), showing that hybrid plants were more tolerant against salinity.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In this study, we found that the hybrid of B. napus resulted in the promotion of seed germination and seedling growth under salt stress (Figures 1A-D), which were confirmed by the alleviation of reduction in plant height (Figure 1E), chlorophyll (Figure 1F), relative water content (Figure 1G), and biomass (Figure 1H). These results in B. napus were consistent with previous studies (Akram et al, 2010;Fujimoto et al, 2012;Bagum et al, 2017;Xu et al, 2018), showing that hybrid plants were more tolerant against salinity.…”
Section: Discussionsupporting
confidence: 92%
“…Improved germination was observed in the hybrid plant of chickpea because of its reduced ROS level (Pandey et al, 2019). In addition, hybrids showed obvious heterosis for photosynthesis under salt stress (Xu et al, 2018). However, very little is known about the corresponding mechanisms regarding heterosis of salinity tolerance in plants.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations